Altered resting-state cerebral blood flow and its relationship with molecular architecture in tremor dominant Parkinson’s disease - Shangpei Wang; Yajie Cai; Yibin Zhao; Yongqiang Yu; Xianwen Chen; Longsheng Wang (Brain Research Bulletin)
Background: The resting-state cerebral blood flow (CBF) alterations in Parkinson’s disease (PD) patients and tremor-dominant (TD) subtype have been explored. However, the underlying molecular architecture correlated with the altered CBF remains unknown. Methods: In total, 90 PD patients including 41 TD subtype, and 90 healthy controls (HC) underwent arterial spin labelling magnetic resonance image. The altered CBF were derived by a voxel-wised two sample t-test compare and spatial correlated with serotonin, dopamine, γ-aminobutyric acid, opioid, noradrenaline, N-methyl-D-aspartic acid, acetylcholine and glutamate neurotransmitter density maps. Results: Compared to HC, PD patients exhibited decreased CBF in left caudate/putamen, increased CBF in bilateral supplementary motor area (SMA). Moreover, the CBF of SMA showed a positive correlation with disease severity. The altered CBF in PD patients were significantly associated with spatial distribution of serotonin 5-hydroxytryptamine receptor, dopamine receptor, and noradrenaline transporter. Compared to non-tremor-dominant subtype, the TD subtype exhibited decreased CBF in left calcarine/cuneus, increased CBF in left middle frontal gyrus and bilateral superior frontal gyrus. The altered CBF in the TD subtype were significantly associated with spatial distribution of serotonin 5-hydroxytryptamine, dopamine, glutamate, and opioid receptors. Conclusions: Besides dopamine, perfusion alterations in SMA of PD patients were more probably correlated with serotonin and noradrenaline. Perfusion alterations of the TD subtype were related to dopamine, serotonin, other excitatory neurotransmitters such as glutamate and opioid, which may provide novel insights into pathophysiological processes and guide new therapeutic targets.